The epidemiological profile of AIDS in Goiás: a state-level analysis (2019–2023) (CIPEEX, 2026)
Introduction: The AIDS epidemic in Brazil has a heterogeneous profile, with regional variations that influence public policies. The state of Goiás presents important particularities that reflect both social vulnerabilities and urban dynamics of transmission. Objective: To analyze the epidemiological profile of AIDS in Goiás between 2019 and 2023, considering temporal trends, demographic distribution, and spatial distribution of cases. Method: Descriptive study based on secondary data from the Notifiable Diseases Information System (SINAN), complemented by state and national epidemiological bulletins. Indicators analyzed included temporal trends, sex, age group, and geographic distribution. Results: Between 2019 and 2023, 2,586 AIDS cases were reported in Goiás. There was temporal fluctuation, with a decline in 2020 attributed to the impact of the COVID-19 pandemic, followed by recovery in 2021–2022. In 2023, an abrupt 63.1% reduction was observed, possibly related to reporting delays. The demographic profile showed a predominance of cases in men (75.8%), with higher concentration in the age groups 20–34 years (45.4%) and 35–49 years (34.6%). Geographically, the epidemic was concentrated in major urban centers: Goiânia (29.7%), Aparecida de Goiânia (10.7%), and Anápolis (7.3%). Conclusions: The state-level analysis shows that AIDS in Goiás remains a significant public health challenge, with a strong concentration among young and urban populations. The fluctuation in records highlights the need for continuous surveillance, overcoming underreporting, and implementing specific prevention and care strategies aimed at the most vulnerable groups.
Keywords: HIV; AIDS; epidemiology; Goiás